Patterns and drivers of water-land resources nexus in arid inland river basins of northwestern China - Lingge Wang; Wei Liu; Qi Feng; Zhenliang Yin; Rui Zhu; Meng Zhu; Jutao Zhang; Yuanyuan Xue; Zexia Chen; Xuejiao Li (Environmental and Sustainability Indicators)
The underlying land surface structure is being reshaped by climate change and human activities, which in turn affects the hydrological processes. However, the patterns and drivers of water and land resources nexus (WLN) in arid inland river basins remain less understood. In this study, we evaluated and predicted water and land resource dynamics by combining the soil quality index function with MCE-CA-Markov and SWAT models. We further constructed the Water-Land Nexus Model (WLNM) for water conservation and consumption zones to quantify responses of WLN to climate and land-use changes in inland river basins. Results showed that the water-land nexus index (WLNI) exhibited decreasing trend from headwaters (water conservation area) to middle and lower reaches (water consumption area). The WLNI decreased in both water conservation and consumption area from 1980 to 2000, with an area-weighted average varying from 0.1105 to 0.1071 for whole basin. It was predicted that the WLNI shows an increasing trend in water conservation area while a decreasing trend in consumption area from 2020 to 2050 under both the natural development (NDS) and ecological protection scenarios (EPS). The Geo-detector analysis showed that soil organic carbon, soil pH and mean annual precipitation are main factors affecting the spatial pattern of WLNI. Furthermore, interactions between natural and socio-economic factors exerted stronger effects on WLNI variations than that of each individual factor, highlighting the importance of interactions between natural factors and human activities in altering water-land resources nexus in arid inland basins.